Managing the female patient with hereditary angioedema. (June 2016) - Banerji, Aleena; Riedl, Marc
Hereditary angioedema (HAE) is a rare disorder resulting from decreased functional levels of C1-inhibitor (C1-INH), which manifests as periodic episodes of localized edema which can be extremely painful, debilitating and even fatal if the swelling affects the larynx. HAE can complicate many aspects of obstetric/gynecologic care, and an awareness of the disease is critical for clinicians involved in the care of women because of potential HAE-related complications pertaining to pregnancy, labor and delivery, and other women's health issues. This article provides a review of published literature specific to HAE and its management in female patients, including important concerns regarding obstetric/gynecologic care. A growing body of relevant experience is presented to help guide the care of women with HAE.